STRENGTHENING ELECTORAL INTEGRITY IN THE CONTEXT OF SPECIAL ECONOMIC ZONES: A LEGAL STUDY ON REGIONAL HEAD ELECTION GOVERNANCE IN BATAM CITY - Erniyanti; Markus Gunawan; M. Tartib; Etty Sri Wahyuni (PT. Radja Intercontinental Publishing, 2026)
This study examines the legal framework governing electoral integrity in regional head elections (Pilkada) in Batam City, a unique administrative region with dual status as both a Free Trade Zone (FTZ) and Special Economic Zone (SEZ). The research addresses the intersection of electoral law, decentralization policies, and special economic governance that creates distinctive challenges for democratic processes. Using normative legal research methodology with statutory, conceptual, and comparative approaches, this study analyzes how the overlapping regulatory frameworks between Law Number 7 of 2017 on General Elections, Law Number 10 of 2016 on Regional Elections, and Government Regulation Number 4 of 2025 on Batam FTZ affect electoral governance and integrity. The findings reveal that Batam faces unique electoral challenges stemming from its heterogeneous population composition, high labor mobility, complex institutional arrangements between Batam Concession Agency (BP Batam) and Batam City Government, and susceptibility to money politics due to economic disparities. This research proposes a legal framework for strengthening electoral integrity through enhanced voter registration mechanisms, improved election supervision coordination, and integrated governance between electoral management bodies and special zone authorities. The study contributes to the scholarly discourse on electoral democracy in special jurisdictions and offers policy recommendations for harmonizing economic zone governance with democratic electoral principles.